Pengaruh Komposisi Media Tanam terhadap Pertumbuhan Taka Asal Kepulauan Seribu Sebagai Bahan Pangan Alternatif - Yenisbar Yenisbar; Luluk P. Ekowahyuni; Umbu Yogi Pratama (Universitas Sebelas Maret, 2020)
Polynesia arrowroot as alternative food resource are rather difficult to be cultivated because of it’s dormant tubers. The propagation needed techniques for growth media optimization to provide a source of planting material. This study aimed to determine the best black Polynesia arrowroot growth from Kepulauan Seribu from several combinations of planting media. The method used was Block Randomized Design (BRD) with planting media treatment (M) : M1 = large granule sand +soil+choarcoal (1: 1:1 v / v), M2 = large granule sand+soil+organic fertilizer (1 : 1: 1 v / v) and M3 = large granule sand +soil+ organic fertilizer (2: 1: 1 v / v). Data were tested by IBM SPSS software version 23 and further tests using DMRT at a level of 5%. The results showed the number leaves increase and plant height increase The best media treatment for number of leaves was large granule sand + soil, while the highest plant height in large granule sand + soil media + manure.